ANALYSIS OF FACTORS AFFECTING CONSUMER USING THE GOJEK APPLICATION - Gustina Hidayat (SINTESA, 2023)
Consumer satisfaction is an evaluation of a person's judgment in the form of feelings of pleasure or disappointment that occur after comparing what is desired for the product or service used with the reality received. anwhile, service quality is something that consistently meets or exceeds consumer expectations. Efforts to improve the service quality of GOJEK drivers need to know the level of customer satisfaction. This study aims to determine the factors that influence customers to use GOJEK services. In this study carried out a qualitative approach. Based on the research results, it was found that the majority of the reliability dimensions applied by GOJEK drivers were in the very good category, GOJEK drivers had implemented the responsiveness aspect very well which focused on providing fast service and driver readiness to help consumers when they needed help. The application of aspects of guarantees that focus on guarantees regarding the friendliness and courtesy of drivers in providing good service to consumers, must be improved so that consumers feel more confident and confident in GOJEK drivers, have implemented aspects of empathy so that consumers feel more respected and valued. And on physical appearance, means of communication, and cleanliness also results in consumers feeling satisfied and comfortable.